2019
DOI: 10.1002/cbdv.201900280
|View full text |Cite
|
Sign up to set email alerts
|

Development of a Headspace Solid‐Phase Microextraction Gas Chromatography‐Mass Spectrometry Method to Study Volatile Organic Compounds (VOCs) Emitted by Lavender Roots

Abstract: A headspace solid‐phase microextraction (HS‐SPME) method combined with gas chromatography‐mass spectrometry (GC/MS) was developed and optimized for the extraction and the analysis of volatile organic compounds (VOCs) from lavandin and fine lavender roots. Optimal parameters to extract volatile molecules from ground and intact roots were determined using a divinylbenzene‐carboxen‐polydimethylsiloxane (DVB/CAR/PDMS) coating fiber at 70 °C for 60 min. A total of 99 VOCs, including 40 monoterpenoids, 15 sesquiterp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
6
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 40 publications
4
6
0
Order By: Relevance
“…DVB‐Carboxen‐PDMS fiber showed higher extraction efficiency for most detected compounds (at different extraction times) compared with that of Carboxen‐PDMS. This observation agrees with the findings of many other studies, where DVB‐Carboxen‐PMDS fiber was used for the extraction of volatile and semivolatile compounds with different molar weights and polarities 31–34 . Porous gold SPME (PG‐SPME) has shown an increase in the peak areas of almost all extracted compounds compared with that of the commercial fibers (Table 1).…”
Section: Resultssupporting
confidence: 91%
See 2 more Smart Citations
“…DVB‐Carboxen‐PDMS fiber showed higher extraction efficiency for most detected compounds (at different extraction times) compared with that of Carboxen‐PDMS. This observation agrees with the findings of many other studies, where DVB‐Carboxen‐PMDS fiber was used for the extraction of volatile and semivolatile compounds with different molar weights and polarities 31–34 . Porous gold SPME (PG‐SPME) has shown an increase in the peak areas of almost all extracted compounds compared with that of the commercial fibers (Table 1).…”
Section: Resultssupporting
confidence: 91%
“…The obtained desorption temperature results agree with the previous studies conducted by other researchers including Schlenoff et al 29 and Nuzzo et al [32][33][34] nanoporous gold SPME is due to the high affinity of alkanethiols, dialkyl sulfides, and dialkyl disulfides to gold (see Table 1). The intensities of detected dialkyl sulfides and dialkyl disulfides were higher than those of alkanethiols, as alkanethiols are more favorable to be adsorbed (at high temperatures) on gold as dialkyl disulfides.…”
Section: Desorption Temperaturesupporting
confidence: 91%
See 1 more Smart Citation
“…Interestingly, in a metabolomic study comparing the emissions of different lavender and lavender roots in the laboratory, β‐phellandrene was shown to be involved in the discrimination between lavender ( maillette , 7713 ) and lavandin ( grosso , abrial ) root species 23 . In our study, β‐phellandrene ( 6 ) was also identified as a marker emitted in greater quantities by the above‐ground parts of lavender.…”
Section: Resultssupporting
confidence: 51%
“…A DVB/CAR/PDMS (divinylbenzene/carboxene/polydimethylsiloxane) fiber was chosen [ 26 , 27 , 28 , 29 ], taking into account a recent study [ 30 ] that concerned the development of a SPME-GC/MS quantitative method to detect alkyl-2-methoxypyrazines (3-isopropyl-2-methoxypyrazine, 3-sec-butyl-2-methoxypyrazine, and 3-isobutyl-2-methoxypyrazine) a class of volatile organic compounds which are the impact compounds of the character of the genus Capsicum [ 31 ].…”
Section: Methodsmentioning
confidence: 99%